ERP recording shows subclinical differences in ADHD patients with and without Tuberous Sclerosis. Issue 1 (January 2019) - Pro, S.; Moavero, R.; Marciano, S.; Vigevano, F.; Curatolo, P.; Valeriani, M.
Abstract : To investigate whether among children and adolescents with attention deficit and hyperactivity disorder (ADHD) those with Tuberous Sclerosis (TS) show specific abnormalities of event-related potentials (ERPs). We recruited 10 ADHD patients: 5 with TS (mean age: 12.6 ± 4.3 years) and 5 without TS (mean age: 11.6 ± 3 years). By using an oddball paradigm, auditory mismatch negativity (MMN) and P3b responses were recorded from Fz and Pz electrodes, respectively. All patients were administered with cognitive, executive functioning, and behavioural questionnaires. No difference was found in cognitive and executive functioning between two groups. The P3b amplitude was significantly higher in TS patients (15.6 ± 9 μV) than in children and adolescents without TS (5.5 ± 2.7 μV) (p = 0.04). The MMN amplitude was higher in TS patients (19 ± 18 μV) than in those without TS (9 ± 6.9 μV), although the difference was not significant (p = 0.3). Our results show that P3 and MMN amplitudes are higher in ADHD patients with TS than in those without TS. This means that among children and adolescents with ADHD involuntary and mostly voluntary attention capabilities are better in those with TS. Since this difference was not found by neuropsychological testing, ERP recording can be useful to unravel subclinical differences between two groups.